فعالية مستخلصات أوراق نبات الزعيتورة Ziziphora tenuior L. تجاه بعض الجراثيم الممرضة - زينب, أسمهان; عيسى, عفيفة; علي, سلمى (Latakia University Journal -Biological Sciences Series, 2016)
تمت دراسة فعالية الخلاصات العضوية (إيتانول وميتانول) لأوراق نبات الزعيتورة Ziziphora tenuior L. تجاه أربع عزلات جرثومية ممرضة عُزلت من عينات مرضية من مختبر مستشفى الأسد الجامعي في اللاذقية بطريقة الإنتشار بالقرص خلال عام 2014.بينت النتائج امتلاك الخلاصات الإيتانولية والميتانولية لأوراق نبات Ziziphora tenuior L. فعالية مضادة لجميع العزلات الجرثومية السالبة والإيجابية غرام. وسجلت حلقات أقطار تثبيط النمو الجرثومي 9 mm تجاه جراثيم Pseudomonas aeruginosa و 44 mm تجاه جراثيم Staphylococcus aureus عند التركيز 200mg/ml للخلاصة الميتانولية، بينما تراوحت أقطار التثبيط في الخلاصة الإيتانولية بين 7 mm عند التركيز 40mg/ml تجاه جراثيم Streptococcus sp. و34mm عند التركيز 200mg/ml تجاه جراثيم Staphylococcus aureus.أكدت النتائج أهمية نبات Ziziphora tenuior L.كمصدر يحتوي مواد طبيعية مضادة للجراثيم الممرضة المدروسة. Activity of Ziziphora tenuior L. leaves organic extracts against four pathogenic bacteria, which were isolated from clinical samples and prepared from Al-Assad hospital laboratory in Lattakia, were tested by disc diffusion method through 2014.Results showed that Ziziphora tenuior L. leaves extracts have antibacterial activity against all Gram positive and negative bacteria. Inhibition zones were recorded between 9mm against Pseudomonas aeruginosa and 44mm against Staphylococcus aureus at concentration of 200mg/ml for the methanolic extract. Whereas the inhibition zones for the ethanolic extract were recorded between 7mm at concentration of 40mg/ml against Streptococcus sp. and 34mm at concentration of 200mg/ml against Staphylococcus aureus.These results represent the importance of Ziziphora tenuior L. as a source of natural substances counteraction of pathogenic bacteria.